Determination of Land Characteristics for Tongka Langit Banana Plant (Musa troglodytarum L.) in Ambon Island - Martha Frelly Wenno; Willem A. Siahaya; Ferad Puturuhu (Faculty of Agriculture, Pattimura University, 2022)
The research was conducted in the villages of Eri, Soya, Kusu-kusu, Waai, Hatu, and Allang of Ambon Island. The aim of this study was to determine the external and internal characteristics of the location for growing Tongka Langit banana (M.roglodytarum L). The method used was a survey method with a free survey observation distance. The results showed that the characteristics of the external land where the Tongka Langit banana plant grows are scattered on the slopes of the foothills with the geology of alluvium, limestone, coral, granite, and loose material. Banana cultivation was associated with mixed garden land use with dominant slopes ranging from flat to gentle (2 - 9%). The research location has a dew point of 24.5 oC - 26.5 oC, humidity 75% - 91%. The internal soil characteristics are as follows: Soil textured slightly coarse to slightly fine, soil reaction was between 6.15 – 7.49, C-organic content was 0.69 - 10.08%, total N content was 0.10 - 0.59 %, C/N ranged from 5-59, P2O5 content was 11-18 ppm, K2O content ranged from 212-295 ppm, and cation exchange capacity was 6.52-24.48 me/100gr.